2019
DOI: 10.1111/andr.12680
|View full text |Cite
|
Sign up to set email alerts
|

Testicular organoids to study cell–cell interactions in the mammalian testis

Abstract: BackgroundOver the last ten years, three‐dimensional organoid culture has garnered renewed interest, as organoids generated from primary cells or stem cells with cell associations and functions similar to organs in vivo can be a powerful tool to study tissue‐specific cell–cell interactions in vitro. Very recently, a few interesting approaches have been put forth for generating testicular organoids for studying the germ cell niche microenvironment.AimTo review different model systems that have been employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…This is in keeping with primary SSC studies showing that SSC resistance to retinoic acid stimulation is contingent on the topography of testis tissue facilitating short range paracrine signaling between specific cell types. [20,21,51] This work illustrates the ability of hiPSCs to generate functional testicular organoids for the first time. We show that testicular somatic cells and SSCs derived from hiPSCs spontaneously organize into miniature tissues that resemble the microarchitecture of native testicular tissue, triggering somatic cell maturation and spermatogenesis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This is in keeping with primary SSC studies showing that SSC resistance to retinoic acid stimulation is contingent on the topography of testis tissue facilitating short range paracrine signaling between specific cell types. [20,21,51] This work illustrates the ability of hiPSCs to generate functional testicular organoids for the first time. We show that testicular somatic cells and SSCs derived from hiPSCs spontaneously organize into miniature tissues that resemble the microarchitecture of native testicular tissue, triggering somatic cell maturation and spermatogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…Expression of the pre-meiotic stage SSC gene STRA8 [49,50] was also noted (Figure 1F), in keeping with reports of primary SSCs grown in monolayer culture. [20,21,51] hiPSC-derived testicular organoid characterization hiPSC-derived testicular cells self-assembled into organoids when cultured overnight in AggreWell™800 microwell plates (Figure 2I), and were transferred to non-adherent plates for suspension culture for 12 days (Figure 2J). The culture medium was designed to mimic in vivo conditions through supplementation with hormones FSH, LH and testosterone, to stimulate somatic cell function and maturation, [52,53] and the Sertoli cell-secreted factors BMP4, SCF and retinoic acid, as studies have shown that these factors are required for SSC entry into differentiation.…”
Section: Cellular Identity Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoids can be derived from induced pluripotent stem cells (iPS cells) and can be used to model normal and abnormal development. For the gonad, iPS cells have been used to generate Sertoli-like cells, and also Leydig and germ cells [ 182 , 183 , 184 , 185 ]. Single-cell RNA-seq could be used to chart the differentiation of these cell types, identifying important genes activated during formation of the testis.…”
Section: Single-cell -Omics In Gonadal Diseasementioning
confidence: 99%
“…Leydig cells and other interstitial cells are also involved in cellular communication within the niche[ 68 - 70 ]. This cell network responds to hormone signals and other signaling in the niche to drive spermatogenesis and testosterone production[ 7 , 71 , 72 ]. The differences in cellular interactions in the testicular microenvironments of different mammals have not yet been clarified[ 73 ], but the testicular microenvironment is essential for spermatogenesis[ 74 ].…”
Section: Spermatogonial Stem Cells and Their Nichementioning
confidence: 99%